IMPROVING THE DISCIPLINE OF TEACHER PERFORMANCE THROUGH MANAGEMENT INFORMATION SYSTEM (SIM)-BASED SUPERVISION AT AR-ROFI'IYYAH ISLAMIC JUNIOR HIGH SCHOOL IN KRAKSAAN, PROBOLINGO - Hasanah , Iradatul; Khumaidi, Ahmad; Herawati (Qawwam : The Leader's Writing, 2025)
The school is facing challenges related to weaknesses in teacher discipline in carrying out daily tasks, such as frequent lateness, lack of reporting on learning activities, and poor classroom management. This study uses a qualitative approach and a school behavior research method conducted in two cycles. The instruments used in this study include observation, interviews, and documentation. The use of a School Information Management System (SIM) was implemented through a simple application that covers online attendance, educational activities, and daily performance assessment. The results showed a significant improvement in teacher discipline, with attendance increasing from 76% to 94% after the implementation of the SIM. Additionally, teachers became more motivated due to increased transparency and a better reporting system. This study concludes that SIM-based supervision and accountability-driven discipline are highly effective in improving teacher performance.